Emerging miniaturized energy storage devices for microsystem applications: from design to integration. (13th October 2020) - Liu, Huaizhi; Zhang, Guanhua; Zheng, Xin; Chen, Fengjun; Duan, Huigao
Abstract: The rapid progress of micro/nanoelectronic systems and miniaturized portable devices has tremendously increased the urgent demands for miniaturized and integrated power supplies. Miniaturized energy storage devices (MESDs), with their excellent properties and additional intelligent functions, are considered to be the preferable energy supplies for uninterrupted powering of microsystems. In this review, we aim to provide a comprehensive overview of the background, fundamentals, device configurations, manufacturing processes, and typical applications of MESDs, including their recent advances. Particular attention is paid to advanced device configurations, such as two-dimensional (2D) stacked, 2D planar interdigital, 2D arbitrary-shaped, three-dimensional planar, and wire-shaped structures, and their corresponding manufacturing strategies, such as printing, scribing, and masking techniques. Additionally, recent developments in MESDs, including microbatteries and microsupercapacitors, as well as microhybrid metal ion capacitors, are systematically summarized. A series of on-chip microsystems, created by integrating functional MESDs, are also highlighted. Finally, the remaining challenges and future research scope on MESDs are discussed.